The material returns to partnership: the effects of educational matching on labour market outcomes and gender equality - Malcolm Brynin; Marco Francesconi (University of Essex, Institute for Social and Economic Research (ISER), 2002)
Partnerships continue to be determined by mutual considerations of the economic value of prospective partners. Whereas in the past this worked through property or income, the basis for assessment is now given by several facets of an individuals human capital, some of which are observed only by marriage candidates but not by social researchers. This gives an indication not only of the suitability of a prospective partner but also of that persons employment prospects and future labour market success. Using the first nine waves of the British Household Panel Survey (1991-1999), we employ a two-stage estimation procedure to identify these uncertificated components of human capital first, and then test whether or not they affect labour market outcomes. We find that wages and occupational prestige scores are significantly affected by such unobservables, and that their effects have increasingly become more symmetrical by gender over time. They are also systematically correlated to partners labour market outcomes in a way that may favour women more than men.
Keywords: 330